Exploring Oral English Learning Motivation in Chinese International Students with Low Oral English Proficiency - Xing, Deyu; Bolden, Benjamin (Journal of International Students, 2019)
This study employed narrative inquiry to understand the oral English learning motivation of Chinese international students with low oral English proficiency through their academic acculturation stories. Expectancy-Value Theory served as the theoretical framework to inform the study design and the interpretation of results. Findings suggest all participants’ motivation for oral English learning increased as a result of the newly acquired high subjective value of spoken English during their academic acculturation. However, they experienced high levels of psychological stress during their academic acculturation due to their low oral English proficiency. Further, participants’ perceived expectancy of success for learning oral English declined as their academic acculturation progressed, negatively influencing their oral English learning motivation. Implications for various stakeholders are discussed.